Synergistically enhanced hydrogen evolution electrocatalysis by in situ exsolution of metallic nanoparticles on perovskites - Zhu, Y.; Dai, J.; Zhou, W.; Zhong, Y.; Wang, H.; Shao, Zongping (R S C Publications, 2018)
We report a smart and effective approach to construct nano-sized metal/perovskite hybrids by a facile exsolution process as highly active electrocatalysts towards the alkaline HER. Ni nanoparticle (NP)-decorated La0.4Sr0.4Ti0.9O3-dperovskite (e-LSTN) with an intimate interface, representing a novel prime example of such hybrid catalysts, can synergistically catalyze the HER in basic media whereby La0.4Sr0.4Ti0.9O3-d(LST) promotes water dissociation and Ni NPs (~30 nm) enable favorable hydrogen adsorption for recombination into H2. This work not only brings about a cost-effective HER electrocatalyst, but also more generally opens up new vistas for developing more advanced materials for various applications in the future.